2011
DOI: 10.1029/2010je003713
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the Martian lower and middle atmosphere as observed by the Mars Climate Sounder: 2. Implications of the thermal structure and aerosol distributions for the mean meridional circulation

Abstract: [1] Retrievals of temperature, dust, and water ice from data collected by the Mars Climate Sounder (MCS) on Mars Reconnaissance Orbiter (MRO) illustrate for the first time the seasonal and diurnal variability of both the thermal structure of the middle atmosphere (above 40 km) and also the vertical distribution of aerosols. These retrievals reveal clear signatures of significant mean meridional cells in the middle and lower atmosphere at both the solstices and equinoxes. We investigate the degree to which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 57 publications
(100 reference statements)
10
45
0
Order By: Relevance
“…stronger local temperature maxima at about 8 Pa and 0°N, and about 0.3 Pa and 60°N, respectively. Both the vortex wall and the polar front now exhibit a distinct lower and middle atmosphere behavior, potentially more consistent with the MCS observations (Heavens et al, 2011), with a primary westerly jet core maximum at about 10 Pa, local westerly jet core minima at about 1 Pa, and an increasing westerly jet again above this level. Local vortex wall temperature maxima and minima correspond to the jet speed minima and maxima, respectively.…”
Section: Simulation Name (And ''Nickname'')supporting
confidence: 74%
See 1 more Smart Citation
“…stronger local temperature maxima at about 8 Pa and 0°N, and about 0.3 Pa and 60°N, respectively. Both the vortex wall and the polar front now exhibit a distinct lower and middle atmosphere behavior, potentially more consistent with the MCS observations (Heavens et al, 2011), with a primary westerly jet core maximum at about 10 Pa, local westerly jet core minima at about 1 Pa, and an increasing westerly jet again above this level. Local vortex wall temperature maxima and minima correspond to the jet speed minima and maxima, respectively.…”
Section: Simulation Name (And ''Nickname'')supporting
confidence: 74%
“…This corresponds to an increase in the polar front temperature maximum and results from an increase in downward vertical motion along the vortex wall. As with the southern summer case, there is good argument for at least partial separation of the circulation at altitudes above about 5 Pa from that below (as argued from MCS data by Heavens et al (2011)). It should be noted that none of the simulations are able to reproduce the magnitude of the upper level temperature maximum over the winter pole (MarsWRF is cooler than observed by about 10 K) or the full penetration of the maximum directly over the geographical pole.…”
Section: Southern Winter Solstice (L S = 90-120°)mentioning
confidence: 88%
“…Finally, Heavens et al . [] studied the kinematic coupling between the mean meridional circulation of the lower and middle atmosphere.…”
Section: Temperature Data Sets From P = 10 Pa To 1×10–4 Pa From Spacementioning
confidence: 99%
“…Observations of the vertical dust distribution of Mars's atmosphere constrain our understanding of the vertical transport of dust and the impact of dust on the circulation at all scales. Retrievals from observations by the Mars Climate Sounder (MCS) onboard the Mars Reconnaissance Orbiter (MRO) have shown that the vertical dust distribution of the tropical atmosphere exhibits a zonal mean climatological feature previously referred to as the high‐altitude tropical dust maximum (HATDM): a detached dust layer (DDL) centered well above the observed height of the daytime planetary boundary layer [see Hinson et al ., ; Tellmann et al ., ], which has an estimated dust mass mixing ratio 2–10 times greater than that of the atmosphere nearer to the surface [ McCleese et al ., ; Heavens et al ., , , ].…”
Section: Introductionmentioning
confidence: 99%